Plication versus Resection in Horizontal Strabismus Surgery: A Systematic Review with Meta-Analysis - Dayane Cristine Issaho; Denise de Freitas; Monica Fialho Cronemberger (Journal of Ophthalmology)
Purpose. The purpose of this review was to compare the efficacy of rectus muscle plication versus resection on the treatment of horizontal strabismus and to evaluate the exodrift after each technique. Methods. A research was performed in Latin American and Caribbean Literature on Health Sciences (LILACS); MEDLINE; and Cochrane Central Register of Controlled Trial (CENTRAL). The database was searched by 30 June 2019. The selection was restricted to articles published in English, Spanish, or Portuguese. There were no date restrictions in the search. A minimum mean follow-up of six months was required to access the primary outcomes. Motor alignment success was defined as postprocedure deviation within 10 prism diopters (PD) of orthotropia. Results. Seven studies were eligible for inclusion. The grouped success rate after plication was 66% (95% CI =  [43%–89%]), and the grouped success rate after resection was 68% (95% CI = [43%–89%]). High heterogeneity was observed between the estimations. There was no difference between the mean amount of deviation corrected in prism diopters, when using the mixed-model approach (SMD = 0.12; 95% CI = −0.2–0.44; p=0.45). The undercorrection rates were also analyzed. The combined odds ratio was 1.37 (95% CI = 0.59–3.16; p=0.462), and there was no statistical significance. Conclusion. Plication of horizontal extraocular muscles reveals to be an alternative to resection in strabismus surgery, with similar results. Exodrift is observed after plication and after resection in the treatment of exotropia, but randomized clinical trials are necessary to analyze and compare the follow-up.